The mediating role of innovation and corporate image in the nexus between corporate social responsibility and marketing performance - Sathana, V. (University of Jaffna, 2024)
This study aims to examine the effects of corporate social responsibility (CSR) on marketing performance, with innovation and corporate image acting as mediators, in the banking sector of Sri Lanka. A quantitative research methodology was employed, and respondents were selected using a convenience sampling method. Data were collected through a survey questionnaire, with bank managers in Sri Lanka serving as the sample unit. Structural equation modeling (SEM) and mediation analysis were conducted to analyze the data. The findings reveal that CSR has a significant positive influence on the marketing performance of banks. Moreover, innovation and corporate image significantly mediate the relationship between CSR and marketing performance. The study underscores the role of CSR in strengthening corporate image and enhancing marketing outcomes. This study also highlights the significance of innovation in enhancing the market performance of the banking industry. This research contributes valuable insights into the nexus between CSR, corporate image, innovation, and marketing performance in the banking sector. While the study focuses on banks, the proposed model could be applicable to other industries. Recognizing innovation as a mediator reinforces the need for banks to take a proactive rather than reactive approach to CSR. Furthermore, the finding that corporate image mediates the CSR-marketing performance link suggests that CSR should be viewed as a strategic investment rather than an expense. A strong corporate image built through CSR can create long-term value and resilience against market fluctuations. This research developed an integrated model based on the theory of the firm perspective, stakeholder theory, and innovation diffusion theory, offering a comprehensive framework for understanding the strategic role of CSR in business performance.
Keywords: Corporate Social Responsibility; Corporate Image; Banking Industry; Innovation; Marketing Performance